2014
DOI: 10.1007/s10654-014-9940-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of adiponectin and leptin with relative telomere length in seven independent cohorts including 11,448 participants

Abstract: Oxidative stress and inflammation are major contributors to accelerated age-related relative telomere length (RTL) shortening. Both conditions are strongly linked to leptin and adiponectin, the most prominent adipocyte-derived protein hormones. As high leptin levels and low levels of adiponectin have been implicated in inflammation, one expects adiponectin to be positively associated with RTL while leptin should be negatively associated. Within the ENGAGE consortium, we investigated the association of RTL with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 62 publications
3
27
0
Order By: Relevance
“…Factors related to socioeconomic status, smoking, alcohol intake or BMI also were not correlated with LTL among controls in our study. While LTL has been associated with BMI and/or smoking in some studies 43, 44, 45 , others (including our prior paper) observed nominal or no significant associations 26, 46, 47, 48, 49 . We observed heterogeneity between cohorts for the intermediate LTL category and used random effects meta-analysis to account for this.…”
Section: Discussionmentioning
confidence: 46%
“…Factors related to socioeconomic status, smoking, alcohol intake or BMI also were not correlated with LTL among controls in our study. While LTL has been associated with BMI and/or smoking in some studies 43, 44, 45 , others (including our prior paper) observed nominal or no significant associations 26, 46, 47, 48, 49 . We observed heterogeneity between cohorts for the intermediate LTL category and used random effects meta-analysis to account for this.…”
Section: Discussionmentioning
confidence: 46%
“…For additional EJE references see [22,26,27,149,[408][409][410][411][412][413][414][415][416][417][418][419][420][421][422][423][424].…”
Section: New Developments: Integrative Genomicsmentioning
confidence: 99%
“…Previously, ethnic disparities in high‐sensitivity C‐reactive protein (hs‐CRP), adiponectin, and insulin resistance (IR) in the local population in Singapore were reported and, interestingly, an increase in body mass index (BMI) was associated with a greater change in hs‐CRP, adiponectin, and IR in Chinese individuals compared with Malays and Indians . Telomere length is inversely associated with BMI and the development of IR, and positively correlated with adiponectin levels . Although ethnic disparities in telomere length have been shown in non‐Asian populations, little is known of ethnic disparities in telomere length in a multiethnic Asian population.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Telomere length is inversely associated with BMI and the development of IR, and positively correlated with adiponectin levels. [17][18][19] Although ethnic disparities in telomere length have been shown in non-Asian populations, little is known of ethnic disparities in telomere length in a multiethnic Asian population. Moreover, the effects of changes in adiposity on telomere length in an Asian population with type 2 diabetes (T2D) are unknown.…”
Section: Introductionmentioning
confidence: 99%